Security Sistem Pada Brankas dengan Metode Personal Identifikasi Number Berpola Aritmatika Modulo - Nurtiyanto, Woro Agus; Rosyani, Perani; Ihksanudin, Moch Koiru (Building of Informatics, Technology and Science (BITS), 2022)
The burglary of a safe in Jombang, East Java, lost valuables belonging to the Multipurpose Business Cooperative (KSU) Niaga Cemerlang. Therefore, a security system tool was made in the safe where it functioned as storing valuables and important assets. Changing the security system using a security system with a personal identification number method with a modulo arithmetic pattern. The safety system of the safe is designed in layers installed with an RFID tag by registering and then verifying it on the card. Entering the password on the card is unreadable or unverified, then the system will refuse to open. Arduino mega component with type 256, passive RFID tag attached to the RFID reader, only 1 validated passive tag can open the security access system with 6 keypad passwords that are inputted only 3. Transistors in the solenoid driver circuit work after the security system is open. The servo motor can rotate according to the input of the 900. open servo angle rotation program